Analysis of key challenges of family businesses : the Croatian context - Mandić, Ana, ekonomistica (Array, 2020)
Family business represents the most common form of the company ownership and makes around 70% to 90% of all firms around the globe depending on the definition one uses. It is estimated that worldwide, family firms account for about 40% to 70% of employment and GDP. The aim of this paper is to provide overview of main characteristics of family business in general and to analyze key challenges family businesses generally are facing today. Additional aim of the paper is to provide overview of research on family business in Croatia and to analyze characteristic and challenges of family businesses in Croatia. Paper provides brief overview of key trends which can have negative implications on companies, their owners, as well as for a wide network of stakeholders such as family members, customers, suppliers, employees, banks, local government and the national economy in general. Some of the challenges discussed in the paper could be relevant to all types of firms. However, with reference to family business these challenges may be more salient than in nonfamily firms or they may need to be addressed differently.